1997
DOI: 10.1038/38738
|View full text |Cite
|
Sign up to set email alerts
|

Sites of alcohol and volatile anaesthetic action on GABAA and glycine receptors

Abstract: Volatile anaesthetics have historically been considered to act in a nonspecific manner on the central nervous system. More recent studies, however, have revealed that the receptors for inhibitory neurotransmitters such as gamma-aminobutyric acid (GABA) and glycine are sensitive to clinically relevant concentrations of inhaled anaesthetics. The function of GABA(A) and glycine receptors is enhanced by a number of anaesthetics and alcohols, whereas activity of the related GABA rho1 receptor is reduced. We have us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

55
980
9
5

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,159 publications
(1,054 citation statements)
references
References 18 publications
55
980
9
5
Order By: Relevance
“…Position 15′ of the 5-HT 3A receptors TM2 domain is a non-pore-facing amino acid residue (Reeves et al, 2001;Panicker et al, 2002). In addition to its role in channel gating, the amino acid residue at 15′ also appears to have important roles in channel modulation by alcohol and anesthetics (Mihic et al, 1997;Wick et al, 1998), and binding of these drugs to a hydrophobic pocket involving this residue alters receptor function. In a separate study, we have demonstrated that L293 is critical for alcohol actions on the 5-HT 3A receptor; and L293C and L293S mutations abolish alcohol modulation (Hu et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Position 15′ of the 5-HT 3A receptors TM2 domain is a non-pore-facing amino acid residue (Reeves et al, 2001;Panicker et al, 2002). In addition to its role in channel gating, the amino acid residue at 15′ also appears to have important roles in channel modulation by alcohol and anesthetics (Mihic et al, 1997;Wick et al, 1998), and binding of these drugs to a hydrophobic pocket involving this residue alters receptor function. In a separate study, we have demonstrated that L293 is critical for alcohol actions on the 5-HT 3A receptor; and L293C and L293S mutations abolish alcohol modulation (Hu et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…2A. Residue L293 is in the same 15′ position as a residue in the GABA A receptor that has important roles in channel gating (Findlay et al, 2001;Scheller & Forman, 2002) and modulation by alcohols and general anesthetics (Mihic et al, 1997;Wick et al, 1998). This amino acid residue is thought to reside on the non-porefacing side of TM2 domain (Panicker et al, 2002;Reeves et al, 2001).…”
Section: Role Of L293 In the Modulatory Action Of 5-himentioning
confidence: 99%
“…A recent study suggests that neuroactive steroids contribute to the hypnotic effects of ethanol in rats (Khisti et al, 2003). Moreover, several studies (Mihic et al, 1997;Koltchine et al, 1999;Mascia et al, 2000;Ueno et al, 2001) have suggested that general anesthesia can be produced, at least in part, by enhancing neuronal inhibition mediated by the GABA A a-2 subunit.…”
Section: Subjective Effects Of Alcoholmentioning
confidence: 99%
“…This is in accordance with the suppression theory. Mihic et al (1997) have by clever use of chimeric constructs localized the binding sites for volatile anesthetics on the GABA channel. But what about the generality of this mechanism?…”
Section: Microscopic Effectsfmodulating Activity Of Critical Ion Chanmentioning
confidence: 99%